Écrire une histoire des employés vietnamiens et indochinois à la Bibliothèque nationale de France - Cao Vy (Moussons)
This research note explores the history of the Indochinese collection at the Bibliothèque nationale de France (BnF), with a particular focus on the Vietnamese and Indochinese employees who worked on these collections between 1942 and 1965. This project is part of a heritage remediation effort aimed at highlighting the contributions of non-European agents in the development of “extra-European” collections. By adopting an inclusive approach, it underscores the central role of these employees in indexing the 25,000 prints of the collection, which were acquired through the legal deposit system in Indochina, and examines the postcolonial dynamics within the BnF. This research draws upon the archives of the General Secretariat of the BnF, particularly the Thérèse Kleindienst collection (1943-1984), which contains previously unexplored documents on the Vietnamese employees and their interactions with the library’s departments.